Photosensitive composition and application thereof

By using grafted polymers, photoacid generators, crosslinking agents and vinyl ether compounds in PSPI materials, it is solved that existing materials are difficult to achieve low temperature curing, high sensitivity, high resolution and low curing simultaneously. The problem of bending stress achieves high sensitivity, resolution and low warping stress of the photosensitive composition, and has high chemical stability and adhesion.

CN119395943APending Publication Date: 2025-02-07JIANGSU AISEN SEMICON MATERIAL CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411509592.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing PSPI materials are difficult to achieve low temperature curing, high sensitivity, high resolution and low warpage stress at the same time.

Method used

Using grafted polymers, photoacid generators, crosslinkers and vinyl ether compounds, the high sensitivity, resolution and low warping stress of the photosensitive composition are achieved through specific structural design and process treatment. .

Benefits of technology

Excellent sensitivity, resolution, and low warpage stress of the photosensitive composition are achieved, and high chemical stability and adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119395943A_ABST
    Figure CN119395943A_ABST
Patent Text Reader

Abstract

The invention provides a photosensitive composition and application thereof. The photosensitive composition comprises a graft polymer, a photoacid generator, a cross-linking agent and a vinyl ether compound, the structure of the graft polymer is shown as a formula 1. The photosensitive composition provided by the invention has excellent sensitivity and resolution, can effectively copy fine patterns, has low warping stress after low-temperature curing, and has high chemical stability and cohesiveness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photosensitive dielectric materials, and in particular relates to a photosensitive composition and application thereof. Background Art

[0002] As semiconductor packaging density increases, PSPI materials are also gradually developing towards low-temperature curing, high sensitivity, high resolution, and low warpage stress. The preparation of PSPI materials with excellent low-temperature curing effect, high sensitivity, high resolution, and low warpage stress has also become a key research direction.

[0003] WO2018225676A1 reports a method of lowering the glass transition temperature of PI polymer and assisting with a thermal alkali generator. This method can achieve low-temperature curing at a temperature of 200-230°C to obtain a negative PSPI cured product with excellent adhesion. However, this method cannot achieve the requirements of high sensitivity, high resolution and low warpage stress.

[0004] CN102575139A discloses a method of using a chemically imidized PI polymer with a phenolic hydroxyl group or a carboxyl group, assisted by a suitable crosslinking agent. This method can achieve low-temperature curing at a temperature of 200-230°C, and obtain a positive PSPI cured product with excellent chemical resistance. However, this method has extremely limited improvement in chemical resistance, and the sensitivity of this composition is generally low.

[0005] WO2008026406A1 discloses a method of using a polymer with phenolic hydroxyl groups, such as poly(p-hydroxystyrene) or phenolic resin, supplemented by a cross-linking agent and toughened with rubber particles, to obtain a composition that cures at 200°C, has a fast sensitivity, a high resolution, and low warping stress. However, the cured product obtained in this way has poor mechanical properties and limited improvement in toughness, which may lead to reliability problems.

[0006] Therefore, how to provide a PSPI material with excellent low-temperature curing effect, high sensitivity, high resolution, and low warpage stress has become an urgent problem to be solved. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a photosensitive composition and its application. The photosensitive composition provided by the present invention has excellent sensitivity and resolution and can effectively replicate fine patterns, and has low warpage stress after low-temperature curing, high chemical stability and adhesion.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a photosensitive composition, comprising a graft polymer (a), a photoacid generator (b), a crosslinking agent (c), and a vinyl ether compound (d);

[0010] The structure of the grafted polymer is shown in Formula 1:

[0011]

[0012] wherein the sum of m and n is an integer of 5-200, such as 5, 10, 15, 20, 25, 35, 40, 50, 70, 75, 80, 85, 95, 100, 110, 120, 135, 150, 160, 175, 180, 185, 190, 195 or 200, etc., n / (m+n) is 0.05-1, such as 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1, etc., k is an integer of 2-10, such as 2, 3, 4, 5, 6, 7, 8, 9 or 10, etc., but is not limited to the values ​​listed above, and other values ​​not listed within the above numerical range are also applicable, Indicates the group attachment site.

[0013] The Ar1 is selected from any one of the groups shown in Formula 2-1 to Formula 2-9, the same or different each time it appears:

[0014]

[0015] In the formula, R1-R8 are independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, X is independently selected from any one of oxygen atom, C1-C5 substituted or unsubstituted alkylene, sulfur atom, sulfone group or carbonyl group; the substituted substituent is selected from halogen or C1-C2 alkyl.

[0016] The Ar2 is selected from any one of the groups shown in Formula 3-1 to Formula 3-12, the same or different each time it appears:

[0017]

[0018] In the formula, R9-R 20 is independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, and Y is independently selected from any one of oxygen atom, C1-C5 substituted or unsubstituted alkylene, sulfur atom, sulfone group or carbonyl group.

[0019] The compound shown in Formula 1 is soluble in alkaline aqueous solution, and its solubility is derived from phenolic hydroxyl groups, so it is preferred to contain a certain proportion of structures, and more preferably k=2 to 10. Too large a k unit will cause a certain film thickness loss in the exposed area, resulting in an inability to effectively replicate the pattern. Therefore, by adjusting the grafting amount of p-hydroxystyrene, the dissolution rate of the polymer in the alkaline aqueous solution changes, so that a photosensitive grafted composition with a moderate dissolution rate can be obtained.

[0020] Further, the polymer m+n is the number of repeating structural units of component (a), and the value of m+n is 5 to 200. When m+n is less than 5, the viscosity of the composition is too low, resulting in the composition being unable to be used as a thick film, and when m+n is greater than 200, the composition becomes too viscous, affecting coating.

[0021] When the structures represented by Formula 1 each contain fluorine atoms greater than or equal to 10% by weight, during development with an alkaline aqueous solution, an appropriate degree of water resistance is exhibited at the interface of the film to prevent penetration at the interface. However, when the content of fluorine atoms exceeds 20% by weight, the solubility in alkaline aqueous solutions is reduced. Therefore, the fluorine atom content is preferably 10-20% by weight.

[0022] The molecular weight of component (a) is preferably 3000 to 200000, more preferably 5000 to 100000, as a weight average molecular weight. The molecular weight here is a value measured by gel permeation chromatography and converted from a standard polystyrene calibration curve.

[0023] In the present invention, the graft polymer having the structural unit shown in Formula 1 is generally prepared by polycondensation of dianhydride and diamine to obtain a polyamic acid polymer, which is then chemically imidized to obtain a polyimide polymer, which is then chloromethylated and xanthate-esterified to obtain a macromolecular initiator, and then grafted polymerized to obtain a graft copolymer of polyimide-g-poly(p-hydroxystyrene).

[0024] Specifically, in the first step, polyamic acid can be prepared by reacting diamine with dianhydride, and then polyimide can be prepared by chemical imidization. In the second step, polyimide is chloromethylated and xanthate-esterified to obtain a macroinitiator. In the third step, the macroinitiator prepared in the second step is grafted with p-hydroxystyrene through RAFT polymerization to prepare a grafted polymer.

[0025] The part of the above-mentioned specific photosensitive composition exposed to ultraviolet light is easily soluble in an alkaline aqueous solution, while the part not exposed to ultraviolet light is insoluble in an alkaline aqueous solution, so that fine patterns can be effectively replicated; and the photosensitive composition of the present invention increases the dissolution rate ratio (dissolution contrast) of the exposed part of the pattern to the unexposed part relative to the alkaline developer, thereby making the product excellent in sensitivity and resolution; the product has low warpage stress, high adhesion and good chemical resistance after low-temperature curing (180-200°C).

[0026] Preferably, R1-R8 are independently selected from any one of hydrogen, fluorine atom, methyl or trifluoromethyl, and X is independently selected from any one of oxygen atom, methylene, sulfur atom, sulfone group, carbonyl group, -C(CH3)2 or -C(CF3)2.

[0027] Specifically, Ar1 is a tetravalent organic group, generally a residue of tetracarboxylic dianhydride or its derivatives with an amide ester structure formed by tetracarboxylic dianhydride or its derivatives and a diamine, preferably a tetravalent aromatic group, preferably a residue of tetracarboxylic dianhydride or its derivatives having the following structure, wherein all four binding sites are present on the aromatic ring. Examples of such tetracarboxylic dianhydrides include: pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2',3,3'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane Dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, bis(3,4-dicarboxyphenyl)ether dianhydride, 1,2,5,6-naphthalenetetracarboxylic acid dianhydride, 9,9-bis(3,4-dicarboxyphenyl)fluorene dianhydride, 9,9-bis{4-(3,4-dicarboxyphenoxy Aromatic tetracarboxylic dianhydrides such as 2,2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride and the like, and aliphatic tetracarboxylic dianhydrides such as butanetetracarboxylic dianhydride and 1,2,3,4-cyclopentanetetracarboxylic dianhydride and the like can be used alone or in combination of two or more.

[0028] Preferably, the R9-R 20 is independently selected from any one of hydrogen, fluorine atom, methyl or trifluoromethyl, and Y is independently selected from any one of oxygen atom, methylene, sulfur atom, sulfone group, carbonyl group, -C(CH3)2 or -C(CF3)2.

[0029] Furthermore, in Formula 1, Ar2 is a divalent organic group, generally an amide structure formed by an amino acid and a diamine, and is derived from an amino acid residue, preferably a divalent aromatic group, preferably an amino acid residue having the following structure, wherein both binding sites are present on the aromatic ring, and such amino acids include p-aminobenzoic acid, m-aminobenzoic acid, ortho-aminobenzoic acid, etc. They can be used alone or in combination of two or more.

[0030] In addition, in order to improve adhesion to the substrate, as long as the heat resistance is not damaged, the Ar2 part can be selected to copolymerize with a certain proportion of aliphatic groups with a siloxane structure, preferably 1-10 mol% of bis(3-aminopropyl)tetramethyldisiloxane, bis(p-aminophenyl)octamethylpentasiloxane, etc.

[0031] The terminal groups of the aromatic polyamide shown in Formula 1 are carboxylic acid or amine depending on the input ratio of Ar1 and Ar2. As required, one or two end-capping agents may react with the polymer ends to make one or both ends saturated aliphatic groups, unsaturated aliphatic groups, carboxyl groups, phenolic hydroxyl groups, sulfonic acid groups or mercapto groups, etc. In this case, the end-capping rate is preferably 30-100%.

[0032] In the present invention, the photoacid generator of component (b) is a compound that generates acid when irradiated with active light or radiation. These can also be used in combination of two or more. In addition, in order to adjust the sensitivity, a sensitizer, etc. can be used in combination.

[0033] Among them, triarylsulfonium salts are particularly preferred photoacid generators from the viewpoint of thermal stability and photosensitivity, and it is more preferred to use a sensitizer in combination. Two or more of these compounds may be used in combination as required.

[0034] Examples of the sulfonate anion contained in the triarylsulfonium salt contained in the composition of the present invention include arylsulfonate anions substituted with a fluorine atom or an organic group having a fluorine atom, and alkanesulfonate anions.

[0035] Specific examples are given below, but the present invention is not limited thereto.

[0036]

[0037] Diaryliodonium salts are also optional photoacid generators, examples of which include diphenyliodonium trifluoroacetate, diphenyliodonium trifluoromethanesulfonate, 4-methoxyphenylphenyliodonium trifluoromethanesulfonate, 4-methoxyphenyliodonium trifluoroacetate, phenyl, 4-(2'-hydroxy-.1'-tetradecyloxy)phenyliodonium trifluoromethanesulfonate, and the like.

[0038] Imidosulfonate derivatives are also optional photoacid generators, including trifluoromethylsulfonyloxybicyclo[2.2.1]heptane-5-terminal dicarboximide, succinimide trifluoromethylsulfonate, phthalimide p-toluenesulfonate, phthalimide trifluoromethylsulfonate, N-hydroxynaphthalimide methanesulfonate, and N-hydroxy-5-norbornene-2,3-dicarboximide propanesulfonate.

[0039] Among the photoacid generators, oxime compounds are preferred, and oxime sulfonate compounds are more preferred from the viewpoints of sensitivity, resolution, dielectric constant, dimensional stability, etc. As the oxime sulfonate compound, i.e., a compound having an oxime sulfonate residue, a compound having an oxime sulfonate residue represented by the following formula can be preferably exemplified:

[0040]

[0041]

[0042] The photoacid generators may be used alone or in combination of two or more. When two or more are used in combination, it is preferred that the photoacid generators be used in combination to generate two or more compounds having different total atomic numbers excluding hydrogen atoms.

[0043] The photosensitive composition provided by the present invention contains a crosslinking agent for the purpose of easily obtaining a cured film, which is a crosslinking agent having a -CH2OR (R is a hydrogen atom or a monovalent organic group) group, and the compound only needs to have one or more of the group, but preferably has two or more. In the heat treatment process after coating, exposing and developing the photosensitive polymer composition of the present invention, it reacts with the polymer as component (a) to crosslink, or a compound that polymerizes itself in the heat treatment process. In addition, the crosslinking agent has an affinity for alkaline aqueous solutions and can increase the dissolution rate in alkaline aqueous solutions.

[0044] Preferably, the cross-linking agent is selected from the compound shown in Formula 4-2-1 or Formula 4-2-2:

[0045]

[0046] Among them, each R 21 , R 22 are independently monovalent organic groups, preferably any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, R 21 , R 22 Exist independently or connect to form a ring structure.

[0047] R 23 is selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, R 24is selected from any one of halogen, C1-C5 substituted or unsubstituted alkyl, a is an integer of 1-4, b is an integer of 0-3, and the sum of a and b does not exceed 4; when a is 2, 3 or 4, each R 23 The same or different, when b is 2 or 3, each R 24 are the same or different; X is selected from any one of C1-C10 substituted or unsubstituted alkyl, C2-C10 substituted or unsubstituted alkylene, and C6-C30 substituted or unsubstituted arylene.

[0048] The following formula 4-2-1-1 shows specific examples of the compound represented by formula 4-2-1. These compounds can be used alone or in combination of two or more.

[0049]

[0050] Among them, R 25 is an alkyl group having 1 to 20 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms, R 26 It is an alkyl group having 1 to 10 carbon atoms.

[0051] The following formula 4-2-2-1 shows specific examples of the compound represented by formula 4-2-2. These compounds can be used alone or in combination of two or more.

[0052]

[0053] In formula 4-2-2, as the 1-4 valent organic group of X, there can be listed an alkyl group having 1-10 carbon atoms, an alkylene group having 2-10 carbon atoms (such as ethylene), an arylene group having 6-30 carbon atoms (such as phenylene), or a group obtained by replacing part or all of the hydrogen atoms of these hydroxy groups with halogen atoms such as fluorine atoms, and these groups may further include phenyl, sulfone, carbonyl, ether bond, thioether bond, amide bond, etc. R 23 Preferably, it is hydrogen, alkyl or alkenyl. The number of carbon atoms in the alkyl or alkenyl group is preferably 1 to 20. 24 It is preferably an alkyl group, an alkenyl group, an alkoxyalkyl group or a hydroxymethyl group, and the number of carbon atoms is preferably 1-20.

[0054] The purity of the compound represented by the above formula 4-2-1 and 4-2-2 is preferably 75% or more, more preferably 85% or more. When the purity is 85% or more, the storage stability is excellent, and the crosslinking reaction of the polyimide composition can be fully carried out. In addition, since the unreacted groups that become water-absorbing groups can be reduced, the water absorption of the polyimide composition can be reduced. As a method for obtaining a high-purity thermal crosslinking agent, recrystallization, distillation, etc. can be cited. The purity of the thermal crosslinking agent can be obtained by liquid chromatography.

[0055] Preferably, the structure of the vinyl ether compound is as shown in Formula 5:

[0056]

[0057] Wherein Y is selected from any one of a C6-C12 substituted or unsubstituted aromatic ring, a C3-C12 substituted or unsubstituted alicyclic ring, and a C1-C5 substituted or unsubstituted alkyl group, c is an integer of 1-5, and d is an integer of 2-4.

[0058] The following formula 5-1 shows specific examples of the compound represented by formula 5. These compounds may be used alone or in combination of two or more.

[0059]

[0060] Preferably, in the photosensitive composition, based on 100 parts by weight of the grafted polymer, the content of the photoacid generator is 1-5 parts, the content of the crosslinking agent is 5-30 parts, and the content of the vinyl ether compound is 5-40 parts.

[0061] The photosensitive composition further comprises a basic compound (e);

[0062] Preferably, in the photosensitive composition, based on 100 parts by weight of the grafted polymer, the content of the basic compound is 0.001-2 parts.

[0063] The ratio of the photoacid generator to the basic compound is preferably acid generator / basic compound (molar ratio) = 2.5-300. That is, from the viewpoint of sensitivity and resolution, the molar ratio is preferably 2.5 or more, and from the viewpoint of suppressing the reduction in resolution caused by the thickening of the relief pattern after exposure to heat treatment over time, it is preferably 300 or less. The acid generator / basic compound (molar ratio) is more preferably 5.0-200, and further preferably 7.0-150.

[0064] Preferably, the basic compound can reduce the change in performance over time from exposure to heating, and can include the following:

[0065] A compound having a structure shown in Formula 6.

[0066]

[0067] A, B, and Q may be any one of an alkyl group, an alkoxy group, and a cyclic alkyl group. The following formula 6-1 shows a specific example of the compound represented by formula 6, and these compounds may be used alone or in combination of two or more.

[0068]

[0069] Preferably, the photosensitive composition further comprises any one of a silane coupling agent (f), a solvent (g) or a leveling agent (h), or a combination of at least two thereof.

[0070] The silane coupling agent is generally an organic silane compound, and examples of the organic silane compound include: γ-aminopropyl trimethoxysilane, γ-aminopropyl triethoxysilane, vinyl triethoxysilane, vinyl trimethoxysilane, γ-glycidyloxypropyl triethoxysilane, γ-glycidyloxypropyl trimethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-acryloxypropyl trimethoxysilane, γ-ureidopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, Methoxysilane, 3-isocyanatepropyltriethoxysilane, bis(2-hydroxyethyl)-3-aminopropyltriethoxysilane, triethoxysilylpropylethyl carbamate, 3-(triethoxysilyl)propylsuccinic anhydride, phenyltriethoxysilane, phenyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, 3-triethoxysilyl-N-(l,3-dimethylbutylene)propylamine, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, etc.

[0071] When the photosensitive composition includes an organic silane compound, the adhesion between the photosensitive composition and the substrate after curing can be improved.

[0072] The solvent is an organic solvent. For example, ketones, esters, lactones, ethers, halogenated hydrocarbons, hydrocarbons, etc. can be used. Specific examples include polar solvents such as γ-butyrolactone, N-methyl-2-pyrrolidone, N-acetyl-2-pyrrolidone, N,N-dimethylacetamide, N,N-dimethyl sulfoxide, hexamethylphosphoric acid triamide, dimethylimidazolidinone, tetraethyl urea, tetramethyl urea, ethyl lactate, 3-methoxy-N,N-dimethylpropaneamide and N-acetyl-ε-caprolactam. Other examples of solvents include acetone, diethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, methyl acetate, ethyl acetate, butyl acetate, diethyl oxalate, diethyl malonate, diethyl ether, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, dichloromethane, 1,2-dichloroethane, 1,4-dichlorobutane, trichloroethane, chlorobenzene, o-dichlorobenzene, hexane, heptane, octane, benzene, toluene, xylene, 1-methoxy-2-propanol, 1-methoxy-2-acetoxypropane, and propylene glycol 1-monomethyl ether 2-acetate. The solvents may be used alone or in combination of two or more.

[0073] The leveling agent is selected from surfactants to improve the coating property between the substrate and the surface. Examples of the surfactant include fluorine-based surfactants such as Fluorad (trade name, manufactured by Sumitomo 3M Co., Ltd.), Megafac (trade name, manufactured by DIC Co., Ltd.), and Surflon (trade name, manufactured by Asahi Glass Co., Ltd.); organic siloxane surfactants such as KP341 (trade name, manufactured by Shin-Etsu Chemical Co., Ltd.), DBE (trade name, manufactured by Chisso Corporation), Polyflow, Glanol (trade name, manufactured by Kyoeisha Chemical Co., Ltd.), and BYK (trade name, manufactured by BYK-Chemie GmbH); acrylic polymer surfactants such as Polyflow (trade name, manufactured by Kyoeisha Chemical Co., Ltd.); and the like.

[0074] Preferably, in the photosensitive composition, based on 100 parts by weight of the grafted polymer, the content of the silane coupling agent is 0.5-10 parts, the content of the solvent is 100-200 parts, and the content of the leveling agent is 100-1000 ppm.

[0075] Next, the method for producing the photosensitive composition provided by the present invention is exemplified. For example, a photosensitive composition can be obtained by uniformly mixing the above-mentioned (a)-(d) components and the (e)-(h) components used as needed. As dissolving methods, stirring and heating can be cited. When heating, it is preferred to set the heating temperature within a range that does not destroy the performance of the composition, usually 10-80°C. In addition, the dissolution order of the components is not particularly limited, and for example, a method of dissolving in sequence starting from compounds with low solubility is included. In addition, for components such as surfactants and a portion of adhesion improvers that are prone to generate bubbles when stirred and dissolved, poor dissolution of other components caused by the generation of bubbles can be prevented by adding them last after dissolving other components.

[0076] The obtained photosensitive composition is preferably filtered using a filter to remove impurities and particles. The filter pore size is 0.5-0.02 μm, for example, 0.5 μm, 0.2 μm, 0.1 μm, 0.05 μm, 0.02 μm, etc., but not limited to this. The material of the filter includes polypropylene (PP), polyethylene (PE), nylon (NY), polytetrafluoroethylene (PTFE), etc., preferably polyethylene and nylon. When the photosensitive composition contains inorganic particles, it is preferred to use a filter with a pore size larger than the particle size of these inorganic particles.

[0077] In a second aspect, the present invention provides a method for manufacturing a pattern, the method comprising coating the photosensitive composition as described above on a supporting substrate, followed by drying, exposing, developing, and heating.

[0078] Preferably, the light source used in the exposure process is i-ray.

[0079] In a third aspect, the present invention provides a cured product, which is formed by curing the photosensitive composition as described above.

[0080] Preferably, the cured product includes a surface protection film and / or an interlayer insulating film.

[0081] The cured product provided by the present invention can be obtained by curing the above-mentioned photosensitive composition. The cured product of the present invention can be used as a patterned cured film or a non-patterned cured film.

[0082] The method for manufacturing a patterned cured film comprises, for example, a step of coating the positive photosensitive composition on a substrate and drying to form a photosensitive polyimide film (film forming step); a step of exposing the photosensitive polyimide film (exposure step); a step of diffusing the photosensitive composition with acid (post-exposure baking step); a step of developing the exposed photosensitive polyimide film with an alkaline aqueous solution to form a patterned polyimide film (development step); and a step of heating the patterned polyimide film (heating step). The method for manufacturing a non-patterned cured film comprises, for example, the above-mentioned film forming step and heating step. It may also further comprise an exposure step.

[0083] In the film forming process, the positive photosensitive composition is applied on a metal substrate such as Cu, a glass substrate, a semiconductor, a metal oxide insulator (such as TiO2, SiO2, etc.), a supporting substrate such as silicon nitride, etc., for example, by dipping, spraying, screen printing, spin coating, etc. From the viewpoint of operability, the applied positive photosensitive composition can also be used by drying by heating (for example, 90-150° C., 1-5 minutes) using a hot plate, an oven, etc. The supporting substrate can also be cleaned with acetic acid, etc. before coating. The film thickness of the obtained photosensitive polyimide film is preferably 5-20 μm.

[0084] In the exposure step, for example, the photosensitive polyimide film formed on the substrate is irradiated with the above-mentioned active light rays through a mask. From the viewpoint of transparency of the component (a), irradiation with i-rays can be preferably used.

[0085] In the development process, for example, the exposed portion of the photosensitive polyimide film after the exposure process is removed with a developer, thereby patterning the photosensitive polyimide film. As a developer, in the case of an alkali-soluble photosensitive composition, an alkali aqueous solution such as sodium hydroxide, potassium hydroxide, sodium silicate, ammonia, ethylamine, diethylamine, triethylamine, triethanolamine, tetramethylammonium hydroxide (TMAH) and the like can be appropriately used. The alkali concentration of these aqueous solutions is preferably set to 0.1-10% by mass fraction. Furthermore, alcohols or surfactants can also be added to the above-mentioned developer for use. The patterned photosensitive polyimide film is called a patterned polyimide film.

[0086] In the heating process, the photosensitive composition can be cured by heating the pattern polyimide film or the photosensitive polyimide film. In particular, the film obtained by curing the pattern polyimide film is called a pattern cured film. The heating temperature is preferably 150-250°C, preferably less than or equal to 230°C, more preferably greater than or equal to 170°C, and further preferably 180-200°C. The heating time is preferably 20 minutes to 6 hours, more preferably 30 minutes to 3 hours. Multi-stage heating can also be performed. The heat treatment can be performed using, for example, a quartz tube furnace, a hot plate, a rapid thermal annealing furnace, a vertical diffusion furnace, an infrared curing furnace, an electron beam curing furnace, and a microwave curing furnace. In addition, any one of the inert atmospheres such as the atmosphere or nitrogen can be selected, but when carried out under nitrogen, oxidation of the pattern can be prevented, so an inert atmosphere such as nitrogen is preferred.

[0087] In a fourth aspect, the present invention further provides an electronic component, wherein the electronic component comprises the cured product as described above.

[0088] The interlayer insulating film and the surface protection film of the present invention can be used for electronic components, etc., and the electronic components of the present invention can be used for semiconductor devices, etc. The semiconductor device can be used for various electronic devices, etc. For example, the schematic diagram of its packaging structure is as follows Figure 1 As shown (wherein the first passivation layer and the second passivation layer adopt the cured product).

[0089] This exhibits excellent rust prevention and adhesion effects on a supporting substrate (particularly a copper substrate or a copper alloy substrate), and can suppress discoloration of the cured film or the supporting substrate (particularly a copper substrate or a copper alloy substrate).

[0090] As the semiconductor device, for example, semiconductor packages such as wafer level chip size package (WLCSP) and fan-out wafer level package (FOWLP) can be cited. In addition, the interlayer insulating film and surface protection film of the present invention can also be used for a circuit forming substrate, and the circuit forming substrate can be used for a hard disk drive suspension, a flexible wiring board, etc.

[0091] Compared with the prior art, the present invention has the following beneficial effects:

[0092] The present invention provides a photosensitive composition which has excellent sensitivity and resolution and can effectively replicate fine patterns, has low warpage stress after low-temperature curing, and has high chemical stability and adhesion. BRIEF DESCRIPTION OF THE DRAWINGS

[0093] Figure 1 It is a schematic structural diagram of a semiconductor device prepared by the solidified material provided by the present invention. DETAILED DESCRIPTION

[0094] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0095] The following is an explanation of some of the terms:

[0096] ODA: 4,4-diaminodiphenyl ether

[0097] SiDA: 1,3-bis(3-aminopropyl)tetramethyldisiloxane

[0098] ODPA: 4,4'-oxydiphthalic anhydride

[0099] Py: pyridine

[0100] Et2A: Acetic anhydride

[0101] PhA: Phthalic anhydride

[0102] NMP: N-methyl 2-pyrrolidone

[0103] TMAH: Tetramethylammonium hydroxide

[0104] CMM: Chloromethyl methyl ether

[0105] SnCl4: Tin tetrachloride

[0106] AIBN: Azobisisobutyronitrile

[0107] 4-HS: p-Hydroxystyrene

[0108] St:Styrene

[0109] 6FAP: 3,3-diamino-4,4-dihydroxydiphenyl-hexafluoropropane

[0110] Preparation Example 1

[0111] Under a dry nitrogen stream, 20.02 g (0.1 mol) of ODA was dissolved in 200 g of NMP, and the resulting solution was cooled to -10°C. Subsequently, 26.37 g (0.085 mol) of ODPA was slowly added thereto so that the temperature of the reaction solution did not exceed 0°C, and stirring was continued for 3 hours, and then 4.44 g (0.03 mol) of PhA was added, and stirring was continued for 2 hours at room temperature to obtain a polyamic acid solution.

[0112] 39.55 g of Py and 30.6 g of Et2A were added to the polyamic acid solution, the temperature was raised to 120°C, and the reaction was continued for 12 hours. After the reaction was completed, the solution was poured into 2 L of deionized water for precipitation, washed with water, and vacuum dried at 80°C to obtain a polyimide resin.

[0113]

[0114] Dissolve 5g of dried polyimide resin in 30mL of dichloroethane, add 80μL SnCl4, heat to 70℃, slowly drop 3mL of CMM into the system, and stir for 5h. After the reaction is completed, pour the solution into 300mL of methanol for precipitation, wash, and dry at 80℃ for 12h to obtain chloromethylated polyimide resin.

[0115]

[0116] Dissolve 1g of dried chloromethylated polyimide resin in 20mL NMP. After dissolution, add 0.1g potassium ethyl xanthate and react at room temperature for 24h. After the reaction is completed, pour the solution into 200mL deionized water for precipitation and dry at 80℃ for 12h to obtain a macromolecular initiator.

[0117]

[0118] Dissolve 1g of the dried macromolecular initiator in 20mL of NMP. After dissolution, heat to 65°C, drop 3g of 4-HS, and then add 0.01g of AIBN to carry out RAFT polymerization, and continue the reaction for 2h. After the reaction is completed, cool the solution to room temperature, pour it into 200mL of deionized water for precipitation, wash it with ethanol several times, and dry it at 80°C for 12h to obtain polyimide-g-poly(p-hydroxystyrene) graft copolymer A1.

[0119]

[0120] The specific test method is as follows:

[0121] (1) Determination of molecular weight

[0122] The number average molecular weight was determined by gel permeation chromatography (GPC) under the following conditions using standard polystyrene conversion. The number average molecular weight of polymer A was 39,000. The measurement was performed using 1 mL of a solution containing 0.5 mg of A and a solvent of [tetrahydrofuran (THF) / dimethylformamide (DMF) = 1 / 1 (volume ratio)].

[0123] Measuring device: Detector L4000UV manufactured by Hitachi, Ltd.

[0124] Pump: L6000 manufactured by Hitachi Manufacturing Co., Ltd.

[0125] C-R4A Chromatopac manufactured by Shimadzu Corporation

[0126] Measurement conditions: Chromatographic column Gelpack GL-S300MDT-5 × 2

[0127] Eluent: THF / DMF=1 / 1 (volume ratio), LiBr (0.03 mol / L), H3PO4 (0.06 mol / L)

[0128] Flow rate: 1.0 mL / min, detector: UV270 nm

[0129] (2) Determination of grafting ratio n / (m+n)

[0130] In addition, NMR measurement was performed under the following conditions, and the grafting ratio of A1 was calculated to be 40%.

[0131] Measurement equipment: AV400M manufactured by Bruker BioSpin

[0132] Magnetic field strength: 400MHz

[0133] Reference material: Tetramethylsilane (TMS)

[0134] Solvent: dimethyl sulfoxide (DMSO)

[0135] (3) Determination of grafting amount k

[0136] The grafting amount of A1 was calculated by NMR measurement under the following conditions: k = 3.5

[0137] Measurement equipment: AV400M manufactured by Bruker BioSpin

[0138] Magnetic field strength: 400MHz

[0139] Reference material: Tetramethylsilane (TMS)

[0140] Solvent: dimethyl sulfoxide (DMSO)

[0141] Comparative Preparation Example 1

[0142] Add 192g methanol, 172.32g 4-HS, 19.53g St and 15g AIBN to a four-necked flask in turn, and stir to dissolve until clear. Vacuum and replace the air in the reaction vessel with nitrogen, heat to 75°C, react for 18h, and stop the reaction. Slowly add the prepared sodium methoxide (0.4g) solution to the reaction system, react for 6h, extract twice with n-heptane and the reaction liquid in a mass ratio of 1:1, remove the unreacted monomers and initiators in the reaction liquid, replace the methanol in the reaction liquid with PGMEA, and obtain the PGMEA solution of the required concentration. PHS resin A2 is obtained, and the ratio of hydroxystyrene to styrene repeating units is 80 / 20.

[0143]

[0144] Comparative Preparation Example 2

[0145] Under a dry nitrogen stream, 36.63 g (0.1 mol) of 6FAP was dissolved in 200 g of NMP, and the resulting solution was cooled to -10°C. Subsequently, 26.37 g (0.085 mol) of ODPA was slowly added thereto so that the temperature of the reaction solution did not exceed 0°C, and stirring was continued for 3 hours, and then 4.44 g (0.03 mol) of PhA was added, and stirring was continued for 2 hours at 20°C to obtain a polyamic acid solution.

[0146] 39.55 g of Py and 30.6 g of Et2A were added to the polyamic acid solution, the temperature was raised to 120°C, and the reaction was continued for 12 hours. After the reaction was completed, the solution was poured into 2 L of deionized water for precipitation, washed with water, and vacuum dried at 80°C to obtain polyimide resin A3.

[0147]

[0148] Examples 1-15 and Comparative Examples 1-3

[0149] The photosensitive compositions of Examples 1 to 15 and Comparative Examples 1 to 3 were prepared according to the components and blending amounts shown in Tables 1 to 3. The amounts in the table are parts by mass of each component relative to 100 parts by mass of component (a).

[0150] The components used are as follows.

[0151] Component (b): Photoacid generator

[0152]

[0153]

[0154] Component (c): thermal crosslinking agent

[0155]

[0156] Component (d): Vinyl ether compounds

[0157]

[0158]

[0159] Ingredient (e): basic compound

[0160] DIA: 2,6-diisopropylaniline

[0161] PEA: N-phenyldiethanolamine

[0162] Component (f): Silane coupling agent

[0163] f1: γ-ureapropyltriethoxysilane

[0164] Ingredients (g): Solvent

[0165] g1: GBL (γ-butyrolactone)

[0166] g2: EL (ethyl lactate)

[0167] Table 1

[0168]

[0169]

[0170] Table 2

[0171]

[0172]

[0173] Table 3

[0174]

[0175]

[0176] The performance of the photosensitive compositions prepared in the examples and comparative examples was evaluated as follows:

[0177] (1) Preparation of developing film

[0178] The photosensitive composition (varnish) prepared in the examples and comparative examples was spin-coated on an 8-inch silicon wafer and then heat-treated (prebaked) at 120°C for 3 minutes using a hot plate (coating and developing device Mark-7 manufactured by Tokyo Electron Ltd.) to prepare a prebaked film with a thickness of 6 μm. An i-line stepper (manufactured by Nikon Corporation, NSR-2005i9C) was used at 50 to 400 mJ / cm 2 Exposure, 10mJ / cm 2 The obtained prebaked film was exposed in steps of . After exposure, the photosensitive composition was exposed at 100° C. for 1 minute and then baked. After the photosensitive composition was baked after exposure, it was developed for 90 seconds using a 2.38 wt % tetramethylammonium (TMAH) aqueous solution (manufactured by Mitsubishi Gas Chemical Co., Ltd., ELM-D), and then rinsed with pure water to obtain a developed film.

[0179] (2) Film thickness measurement method

[0180] The film thickness after prebaking and after development was measured using a film thickness measuring device Filmtris F50 at a refractive index of 1.63.

[0181] (3) Determination of warpage

[0182] The varnish was applied by spin coating using a coating and developing device ACT-8 and prebaked so that the film thickness after prebaking at 120°C for 3 minutes was 10 μm. Then, the temperature was raised to 200°C at a rate of 3.5°C / min under the condition of an oxygen concentration of 20 ppm or less using an inert oven, and heat-treated at 200°C for 1 hour. When the temperature became 50°C or less, the wafer was taken out and the cured film was measured using a pressure device FLX2908 (manufactured by KLA Tencor). As a result, the case of 35 MPa or more was considered insufficient (D), the case of 30 MPa or more and less than 35 MPa was considered good (C), the case of 20 MPa or more and less than 30 MPa was considered better (B), and the case of less than 20 MPa was considered the best (A).

[0183] (4) Sensitivity evaluation

[0184] After exposure and development, the exposure amount (called the optimal exposure amount Eop) that forms a 20μm line and space pattern (1L / 1S) with a width of 1:1 is used as the sensitivity. 2 Below 150 mJ / cm2, it can be judged as high sensitivity. More preferably, it is 150 mJ / cm2. 2 The results are shown in Table 4 below.

[0185] (5) Chemical resistance evaluation

[0186] Apply to the above solidified product with a pipette. Place the solidified product after application in a nitrogen oven at 200°C and keep it for 60 minutes. Then, transfer the solidified product from the hot plate and cool it to room temperature. Wash the cooled solidified product with NMP at 45°C and soak it for 1 hour, then measure the film thickness.

[0187] The film thickness change rate (%) was calculated from the film thickness change. A positive value means that the film expanded, and a negative value means that the film dissolved. The results are shown in Table 4.

[0188] (6) Adhesion evaluation

[0189] A cured product was produced on a Cu substrate using the above-mentioned method for producing a cured product. The cured product was cut into 10×10 grids using a crosscut guide (manufactured by COAT-TECH Co., Ltd.) with a shear knife, thereby dividing the cured product into 100 small pieces.

[0190] An adhesive tape (manufactured by 3M Japan Ltd.) was attached to the cured product, and then the adhesive tape was peeled off. The adhesiveness was evaluated as follows based on the number of small pieces of the cured product peeled off from the substrate when the adhesive tape was peeled off.

[0191] A: The number of remaining grids is 100 to 80.

[0192] B: The number of remaining grids is less than 80.

[0193] The results are shown in Table 4.

[0194] (7) Evaluation of elongation at break

[0195] The varnish was applied by spin coating using a coating and developing device ACT-8 and prebaked to a film thickness of 10 μm after prebaking at 120°C for 3 minutes. Then, the temperature was raised to 200°C at a rate of 3.5°C / min under an oxygen concentration of 20 ppm or less using an inert oven, and heat treated at 200°C for 1 hour. When the temperature became below 50°C, the wafer was taken out, the film was peeled off, and cut into 4 mm × 8 mm strips, and tensile testing was performed using DAGE4000.

[0196] As a result, the case where the elongation at break was 30% or more was regarded as excellent (A), the case where it was 20-30% was regarded as good (B), the case where it was 10-20% was regarded as poor (C), and the case where it was less than 10% was regarded as very poor (D).

[0197] Table 4

[0198]

[0199]

[0200] As can be seen from Table 4, the photosensitive polyimide compositions provided by Examples 1-15 of the present invention all have high sensitivity, excellent low warpage stress, and excellent chemical resistance. Compared with the examples, Comparative Examples 1 and 2 have poor toughness and poor sensitivity. Comparative Example 3 has high warpage stress, poor sensitivity, and poor chemical resistance.

[0201] The applicant declares that the present invention uses the above embodiments to illustrate the photosensitive composition and its application, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0202] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0203] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

Claims

1. A photosensitive composition, characterized in that The photosensitive composition comprises a graft polymer, a photoacid generator, a crosslinking agent, and a vinyl ether compound; The structure of the grafted polymer is shown in Formula 1: In the formula, the sum of m and n is an integer of 5-200, n / (m+n) is 0.05-1, k is an integer of 2-10, Indicates the group attachment site; The Ar1 is selected from any one of the groups shown in Formula 2-1 to Formula 2-9, the same or different each time it appears: In the formula, R1-R8 are independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, X is independently selected from any one of oxygen atom, C1-C5 substituted or unsubstituted alkylene, sulfur atom, sulfone group or carbonyl group; the substituted substituent is selected from halogen or C1-C2 alkyl; The Ar2 is selected from any one of the groups shown in Formula 3-1 to Formula 3-12, the same or different each time it appears: In the formula, R9-R 20 is independently selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, and Y is independently selected from any one of oxygen atom, C1-C5 substituted or unsubstituted alkylene, sulfur atom, sulfone group or carbonyl group.

2. The photosensitive composition according to claim 1, characterized in that The R1-R8 are independently selected from any one of hydrogen, fluorine atoms, methyl or trifluoromethyl groups, and X is independently selected from any one of oxygen atoms, methylene, sulfur atoms, sulfone groups, carbonyl groups, -C(CH3)2 or -C(CF3)2.

3. The photosensitive composition according to claim 1 or 2, characterized in that The R9-R 20 is independently selected from any one of hydrogen, fluorine atom, methyl or trifluoromethyl, and Y is independently selected from any one of oxygen atom, methylene, sulfur atom, sulfone group, carbonyl group, -C(CH3)2 or -C(CF3)2.

4. The photosensitive composition according to any one of claims 1 to 3, characterized in that: The cross-linking agent is selected from the compound shown in Formula 4-2-1 or Formula 4-2-2: Among them, each R 21 , R 22 are independently monovalent organic groups, R 21 , R 22 Exist independently or connect to form a ring structure; R 23 is selected from any one of hydrogen, halogen, C1-C5 substituted or unsubstituted alkyl, R 24 is selected from any one of halogen, C1-C5 substituted or unsubstituted alkyl, a is an integer of 1-4, b is an integer of 0-3, and the sum of a and b does not exceed 4; when a is 2, 3 or 4, each R 23 The same or different, when b is 2 or 3, each R 24 are the same or different; X is selected from any one of C1-C10 substituted or unsubstituted alkyl, C2-C10 substituted or unsubstituted alkylene, and C6-C30 substituted or unsubstituted arylene.

5. The photosensitive composition according to any one of claims 1 to 4, characterized in that: The structure of the vinyl ether compound is shown in Formula 5: Wherein Z is selected from any one of a C6-C12 substituted or unsubstituted aromatic ring, a C3-C12 substituted or unsubstituted alicyclic ring, and a C1-C5 substituted or unsubstituted alkyl group, c is an integer of 1-5, and d is an integer of 2-4.

6. The photosensitive composition according to any one of claims 1 to 5, characterized in that: In the photosensitive composition, based on 100 parts by weight of the graft polymer, the content of the photoacid generator is 1-5 parts, the content of the crosslinking agent is 5-30 parts, and the content of the vinyl ether compound is 5-40 parts.

7. The photosensitive composition according to any one of claims 1 to 6, characterized in that: The photosensitive composition further comprises a basic compound; Preferably, in the photosensitive composition, the content of the basic compound is 0.001-2 parts by weight based on 100 parts by weight of the grafted polymer; Preferably, the photosensitive composition further comprises any one or a combination of at least two of a silane coupling agent, a solvent or a leveling agent; Preferably, in the photosensitive composition, based on 100 parts by weight of the grafted polymer, the content of the silane coupling agent is 0.5-10 parts, the content of the solvent is 100-200 parts, and the content of the leveling agent is 100-1000 ppm.

8. A method for manufacturing a graphic, characterized in that: The manufacturing method comprises coating the photosensitive composition according to any one of claims 1 to 7 on a supporting substrate, followed by drying, exposing, developing, and heating; Preferably, the light source used in the exposure process is i-ray.

9. A solidified product, characterized in that: The cured product is formed by curing the photosensitive composition according to any one of claims 1 to 7; Preferably, the cured product includes a surface protection film and / or an interlayer insulating film.

10. An electronic component, characterized in that: The electronic component comprises the cured product according to claim 9.

Citation Information

Patent Citations

  • Photosensitive adhesive composition, photosensitive adhesive sheet, and semiconductor devices using same

    CN102575139A

  • Photosensitive insulating resin composition, hardening product thereof, and circuit board equipped therewith

    WO2008026406A1

  • Photosensitive resin composition, cured film, laminate, method for producing cured film, semiconductor device and compound

    WO2018225676A1